Estimated Stock Price Based on Company Communications: Mind Genomics and Cognitive Economics as knowledge-Creation Tools for Behavioral Finance - Moskowitz, Howard; Baum, Edgar; Rappaport, Stephen D; Gere, Attila (Edelweiss Applied Science and Technology, 2019)
Respondents estimated the price of a share of stock for a company, based upon a set of short vignettes, one estimate for each vignette. The vignettes comprised 2-4 elements-statements selected from four groups: WHO presents the information, the company‟s VALUES, how the presenter shows ALIGNMENT with company values, and how CUSTOMERS respond. The linkage between expected dollar value of the st ock and message was highest for the element talking about positive customer reviews. The respondents divide into two groups or mind-sets, based upon their patterns of response to the elements. Mind-Set 1 estimates stock price based on messages communicating „good governance‟. MindSet 2 estimates stock price based on messages communicating „customer intimacy and excitement‟.